Effective Impedance Method for In situ Ellipsometry Analysis of Magnetic Films - L.V. Panina; A.T. Morchenko; L.V. Kozhitov; P.A. Ryapolov (Журнал нано- та електронної фізики)
The method of effective surface impedance is proposed and applied for in situ characterisation of magnetic structures. For any ellipsometry investigations a proper choice of a physical model is important for solving the inverse problem. Reasonable approximations used for in situ ellipsometry monitoring are assumptions of a constant rate of layer growth and stable optical parameters. Standard ellipsometry analysis requires the model response to be calculated from every layer in the structure. Errors from underlying layers propagate through the entire structure and accumulate. In this case a method of a pseudosubstrate is used which approximates the underlying structure as a single interface (so called virtual interface), rather than tracking the entire sample history. The virtual interface is placed at some level and growth is modelled on this interface with no knowledge retained for the underlying structure. There are various methods for describing the virtual interface. In this paper, the concept of the effective impedance is used which requires only three measurement data points and is convenient for combined investigation of optical and magneto-optical properties. The algorithm is based on the calculation of the characteristic matrix of the layer (Abeles matrix) and surface impedance of the virtual interface using two ellipsometric experimental data points. The method is successfully used to analyse Co / SiCo films.